Production of biofuels from microalgae - A review on cultivation, harvesting, lipid extraction, and numerous applications of microalgae. (October 2018) - Enamala, Manoj Kumar; Enamala, Swapnika; Chavali, Murthy; Donepudi, Jagadish; Yadavalli, Rajasri; Kolapalli, Bhulakshmi; Aradhyula, Tirumala Vasu; Velpuri, Jeevitha; Kuppam, Chandrasekhar
Abstract: The concern regarding alternate sources of energy is mounting day-by-day due to the effect of pollution that is damaging the environment. Algae are a diverse group of aquatic organisms have an efficiency and ability in mitigating carbon dioxide emissions and produce oil with a high productivity which has a lot of potential applications in producing biofuel, otherwise known as the third-generation biofuel. These third generation biofuels are the best alternative to the present situation since they have the perspective to eliminate most of the ecological problems created by the use of conventional fossil fuels. These organisms are responsible for closely 50% of the photosynthesis process taking place on the planet and are distributed predominantly in many of the aquatic systems. The huge interest in utilizing these organisms as a potential source of energy lies in converting the primary as well as secondary metabolites into useful products. Algae are considered to be the most prominent resource for the upcoming generations as the most suitable and sustainable feedstock. The key process limitations in microalgal biofuel production are inexpensive and effective harvesting of biomass and extraction of lipids. The major objective of this article is to provide a comprehensive review on various methods of both biomass harvesting and lipid extraction from microalgae available, so far, besides to discuss their advantages and disadvantages. This article also deals with various conditions that are favourable for lipid accumulation as well as the yield from different species. Highlights: Algae are considered as the most prominent resource for the future generations as viable feedstock. Microalgae act as solar driven energy cell factories and are capable of converting CO2 to O2 . The key limit in microalgae biofuel production is cheap and effective extraction of lipids. Existing technical viability for the production of biofuels from microalgae has been discussed. Numerous biomass harvesting and lipid extraction methods were also discussed in detail.